Prevalence and clinical correlates of focal choroidal excavation in eyes with age-related macular degeneration, polypoidal choroidal vasculopathy and central serous chorioretinopathy. Issue 7 (26th October 2015) - Lim, Fiona Pin Miao; Wong, Chee Wai; Loh, Boon Kwang; Chan, Choi Mun; Yeo, Ian; Lee, Shu Yen; Mathur, Ranjana; Wong, Doric; Wong, Tien Yin; Cheung, Chui Ming Gemmy
Abstract : Purpose: To describe the prevalence and clinical characteristics of focal choroidal excavation (FCE) in patients with exudative maculopathy due to age-related macular degeneration with choroidal neovascularisation (AMD-CNV), polypoidal choroidal vasculopathy (PCV) and central serous chorioretinopathy (CSC). Methods: Three hundred and forty-three patients (343 presenting eyes and 255 fellow unaffected eyes) from consecutive patients presenting with untreated AMD-CNV, PCV or CSC are prospectively recruited. Two independent retinal specialists masked to the clinical diagnosis graded the presence of FCE by examining the findings from spectral-domain optical coherence tomography (SD-OCT). The frequency and clinical characteristics of FCE in each of the three clinical diagnosis groups were compared. Results: The diagnosis in the presenting eye was AMD-CNV in 92 patients, PCV in 149 patients, retinal angiomatous proliferation (RAP) in 3 patients and CSC in 99 patients; 255 fellow eyes free of clinical diseases were also graded. The prevalence of FCE was 2.3% (total 14 eyes; 10 presenting eyes, 4 fellow eyes) out of 598 eyes examined. In presenting eyes, FCE was most prevalent in PCV (6.0%), followed by AMD-CNV (1.0%) and CSC (0%), p=0.02. In fellow eyes, the prevalence of FCE was 2.9%, 0% and 1.2% in patients with PCV, AMD-CNV and CSC, respectively. Eyes with FCE had a significantly longer axial length (24.93±1.65 mm vs 23.49±1.10 mm, p<0.001), but otherwise, all other characteristics were similar. Conclusions: FCE is more common in PCV than AMD-CNV and CSC. Disturbance in the choroid/retinal pigment epithelium/Bruch membrane interface affected by FCE may be linked to the pathogenesis of PCV and AMD-CNV.